Representation of Women's Struggles in the Film Gadis Kretek Using Semiotic Analysis: Representasi Perjuangan Perempuan dalam Film Gadis Kretek Menggunakan Analisis Semiotik - Sari, Dea Puspita; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Film, as a powerful mass medium, shapes public views by conveying messages through audio and visual elements. The representation of women in media is a crucial area of study, reflecting societal norms and power dynamics. Specific Background: The Indonesian film